Design of Miniaturized and Polarization-Insensitive Double-Layer Frequency Selective Surface Based on Meander Lines - Feifei Huo; Fei Liu; Min Zhu; Jianhui Bao (International Journal of Antennas and Propagation)
The work presented in this paper concerns a method for the miniaturized frequency selective surface (FSS) based on the meander lines. A miniaturized dual-bandstop FSS structure based on meander lines with spiral-shape is proposed and simulated. The equivalent circuit and current distributions are introduced to explain the FSS performance. The size of the unit cell is 10 mm, which is about 0.037 wavelength at the first resonant frequency. Simulation results indicate that the proposed FSS has a frequency shift smaller than 1% for different polarizations with an oblique incident angle of 60°. A prototype of the FSS is fabricated and measured. The measurement results show that the FSS is polarization-insensitive and angle-insensitive.